Consider the equation below.
4t^2 - 28t = 6t^2 - 12t + 26
Which equation could be used when completing the square to solve for t?

A. (t + 4)^2 = 3
B. (t + 8)^2 = -13
C. t^2 + 8t + 4 = -13 + 4
D. t^2 + 8t + 64 = -13 + 64

Respuesta :

The correct equation that can be used is [tex](t+4)^{2}=3[/tex] ( Option A)

Step-by-step explanation:

Given Equation:

[tex]4 t^{2}-28 t=6 t^{2}-12 t+26[/tex]

It can be rearranged as follows,

[tex]6 t^{2}-4 t^{2}+28 t-12 t+26=0[/tex]

IT can be simplified as,

[tex]2 t^{2}+16 t+26=0[/tex]

Dividing the above equation by 2, we will get,

[tex]t^{2}+8 t+13=0[/tex]

Now we have to divide the coefficient of t by 2, we will get 4 and squaring 4, and add that value on both sides of the equation we will get,

[tex]t^{2}+8 t+16=-13+16[/tex]

[tex]t^{2}+8 t+16=3[/tex]